2007
DOI: 10.1021/jm070361q
|View full text |Cite
|
Sign up to set email alerts
|

Nitrated Indenoisoquinolines as Topoisomerase I Inhibitors:  A Systematic Study and Optimization

Abstract: The biological activity of indenoisoquinoline topoisomerase I (Top1) inhibitors can be greatly enhanced depending on the choice of substituents on the aromatic rings and lactam side chain. Previously, it was discovered that a 3-nitro group and a 9-methoxy group afforded enhanced biological activity. In the present investigation, indenoisoquinoline analogues were systematically prepared using combinations of nitro groups, methoxy groups, and hydrogen atoms in an effort to understand the contribution of each gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
77
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(77 citation statements)
references
References 37 publications
0
77
0
Order By: Relevance
“…57,6163,6568 However, there is very limited study on the modification of the A ring of indenoisoquinoline, especially on the 2-position. To date, the methoxy group is the only substituent that has been placed at the 2-position.…”
Section: Introductionmentioning
confidence: 99%
“…57,6163,6568 However, there is very limited study on the modification of the A ring of indenoisoquinoline, especially on the 2-position. To date, the methoxy group is the only substituent that has been placed at the 2-position.…”
Section: Introductionmentioning
confidence: 99%
“…Indenoisoquinoline derivatives have previously shown antiproliferative properties in various human cancer cell lines and have been considered to be topoisomerase 1 inhibitors. [27][28][29] Herein, we present the design, synthesis, and biophysical and primary biological evaluation of 6-substituted indenoisoquinolines as a new class of G-quadruplex stabilizing ligands. We have synthesized indenoisoquinolines 1a-e from commercially available indeno[1,2-c]isochromene-5,11-dione (2) with excellent yields (Scheme 1) (generally >90%, see the Supporting Information for details).…”
mentioning
confidence: 99%
“…The effect of installation of this group on indenoisoquinoline Top1 poisoning activity was not consistent with observations from previous studies, which have shown that the group can increase activity moderately. 20, 29 …”
Section: Resultsmentioning
confidence: 99%